The impact of hiding information / Siti Khadijah Mazlan and Muhamad Faiz Muhamad Arif - Mazlan, Siti Khadijah; Muhamad Arif, Muhamad Faiz (Faculty of Information Management, 2014)
'Hiding information' has been found at different meanings that, unfortunately, are conflicting and hence potentially misleading. In the disciplines of information management studies, 'hiding information' 'tends to be used to refer to forms of information reflects, which is increased by reducing or eliminating problems. In particular, hiding refers to possibility of accessing information, intentions or behaviour's that have been intentionally exposed through a process of disclosure. For the disciplines of computer science and IT studies, 'hiding information' is more likely to refer to a condition of information difficult to find with the eye, but actually, the information is there actually. It happens when an application or computational process is said to be hidden to the user which information is to be made accessible to some agents by an information provider. Not all information managers in the area of information studies use the expression "information hiding".